Rock You Music: jogo musical sério para crianças autistas - Rocha, Antônio Mairlon Ponte (2023)
Since 1943, when the first study on autism was published by psychiatrist Leo Kanner in his work “Autistic Disorders of Affective Contact”, society has been looking for ways to better integrate these individuals into its dynamics. Not far from that time, in 1944, music therapy emerged, which aims to use sound-musical stimuli to improve communication and stimulate the relationship, motivation and learning of people with disabilities. Today, in the digital age, new ways of educating and preparing are mixed with the classic ones, including serious games, which aim to generate knowledge in a playful, fun and relaxing way. Aiming to contribute to the inclusion of children with the autism spectrum disorder, and also to contribute to this mix between classic and modern, this work aims at the development of a serious game with a theme focused on music and musicality. The game was developed for the Android platform, using the Unity game engine, and contains levels such as: puzzles, memory games, tributes to classic games, stages with augmented reality, among others. The focus of the game is to help in a playful, inclusive and fun way in personal and cognitive development, observing the characteristics of Autism spectrum disorder (ASD), such as difficulty in social communication, restrictive and/or repetitive behaviors, among others. The development of the game also considered treatments for ASD, such as therapy, speech therapy, music therapy, psychomotricity, among others. The game underwent three validations: The first one was made with the analysis of six multidisciplinary specialists divided into two groups (health and technology/games specialists), obtaining an excellent classification by the Content Validity Index (CVI). The second validation was carried out in 3 sessions by 23 children who attend the Associação de Pais e Amigos dos Excepcionais (APAE) in Sobral, with the completion of the EGameFlow instrument by the guardian who accompanied them, obtaining an overall average of 6.36 out of 7.00. The third evaluation was made through the analysis of game statistics when used by APAE children.